The Roman Calendar from Numa to Constantine : Time, History, and the Fasti. - R?pke, J?rg (John Wiley & Sons, 2011)
This book provides a definitive account of the history of the Roman calendar, offering new reconstructions of its development that demand serious revisions to previous accounts. Examines the critical stages of the technical, political, and religious history of the Roman calendar Provides a comprehensive historical and social contextualization of ancient calendars and chroniclesHighlights the unique characteristics which are still visible in the most dominant modern global calendar.